Dear chairman : boardroom battles and the rise of shareholder activism - Gramm, Jeff (New York, NY : Harper Business, 2015)
A sharp and illuminating history of one of capitalism{u2019}s longest running tensions{u2014}the conflicts of interest among public company directors, managers, and shareholders{u2014}told through entertaining case studies and original letters from some of our most legendary and controversial investors and activists.
Benjamin Graham versus Northern Pipeline: the birth of modern shareholder activism -- Robert Young versus New York Central: The proxyteers storm the Vanderbilt line -- Warren Buffett and American Express: the great salad oil swindle -- Carl Icahn versus Phillips Petroleum: the rise and fall of the corporate raiders -- Ross Perot versus General Motors: the unmaking of the modern corporation -- Karla Scherer versus R.P. Scherer: a kingdom in a capsule -- Daniel Loeb and hedge fund activism: the shame game -- BKF Capital: the corrosion of conformity.
Includes bibliographical references (pages 255-275) and index.
Keywords: Corporations -- Investor relations -- United States -- History; Stockholders -- United States -- History; Corporate governance -- United States -- History